1997
DOI: 10.1001/archinte.157.13.1436
|View full text |Cite
|
Sign up to set email alerts
|

Gout and risk for subsequent coronary heart disease. The Meharry-Hopkins Study

Abstract: These results, in black and white male physicians, do not suggest a role in men for targeting gout identification in the primary prevention of CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 17 publications
0
52
0
1
Order By: Relevance
“…8 However, on the other hand, many studies argue that the observed association between uric acid and atherosclerosis is attributable to an indirect association of hyperuricemia with cardiovascular risk factors 9 or clustering of these metabolic and hemodynamic risk factors, designated "metabolic syndrome." 10,11 Although many studies have focused on the presence or absence of an independent relationship between uric acid and coronary and cerebrovascular artery diseases, [12][13][14] thus far, few have examined the independence of the relationship between serum uric acid and carotid atherosclerosis. 15,16 To this end, the current study had 2 goals: first, to investigate the association between uric acid levels and metabolic syndrome in individuals undergoing general health screening; and second, to assess whether there was an independent association of uric acid with the prevalence of carotid plaque in individuals with or without metabolic syndrome after adjusting for other confounding risk factors for atherosclerosis.…”
mentioning
confidence: 99%
“…8 However, on the other hand, many studies argue that the observed association between uric acid and atherosclerosis is attributable to an indirect association of hyperuricemia with cardiovascular risk factors 9 or clustering of these metabolic and hemodynamic risk factors, designated "metabolic syndrome." 10,11 Although many studies have focused on the presence or absence of an independent relationship between uric acid and coronary and cerebrovascular artery diseases, [12][13][14] thus far, few have examined the independence of the relationship between serum uric acid and carotid atherosclerosis. 15,16 To this end, the current study had 2 goals: first, to investigate the association between uric acid levels and metabolic syndrome in individuals undergoing general health screening; and second, to assess whether there was an independent association of uric acid with the prevalence of carotid plaque in individuals with or without metabolic syndrome after adjusting for other confounding risk factors for atherosclerosis.…”
mentioning
confidence: 99%
“…The self report of gout by this physician cohort had excellent concordance with the American College of Rheumatology Criteria for gout [ 14 ]. Gelber et al [ 10 ] adjusted for confounders of cholesterol, smoking, body mass index, alcohol use, hypertension, and diabetes. It was not clear if age was adjusted for in the model.…”
Section: Introductionmentioning
confidence: 64%
“…Three prospective observational cohort studies met the search criteria: 1) Framingham Heart study [ 9 ]; 2) the Meharry-Hopkins study [ 10 ]; 3) The Multiple Risk Factor Intervention Trial (MRFIT) [ 11•• ]; and the Health Professionals Follow-up study [ 12•• ]. The signifi cant heterogeneity among the studies in terms of data collection strategies, case defi nition, and outcome defi nition precluded a formal statistical meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past US and multinational epidemiologic studies have supported [9,19•,52-55] and refuted [56][57][58] an association of elevated serum urate with cardiovascular disease. Furthermore, associations may be seen in only particular patient subgroups, such as for women [53,59] and those with particular body physiques [41].…”
Section: Cardiovascular Diseasementioning
confidence: 99%